Soil health and climate change - Singh, Bhupinder Pal; Cowie, Annette L.; Chan, K. Yin (Springer Berlin Heidelberg, 2011)
Soil Health and Climate Change? presents a comprehensive overview of the concept of soil health, including the significance of key soil attributes and management of soil health in conventional and emerging land use systems in the context of climate change. Starting with a review of the physical, chemical and biological indicators of soil health and their significance for monitoring the impacts of climate change, this book then focuses on describing the role of soil structure, pH, organic matter, nitrogen, respiration and biota in sustaining the basic functions of soil ecosystems, and their anticipated responses to climate change. Further topics include the management of cropping, pastoral, and forestry systems, and rehabilitated mine sites, with a focus on mitigation of and adaptation to climate change impacts. Finally, the opportunities and potential risks of organic farming, biochar and bioenergy systems, and their ability to sustain and even enhance soil health, are discussed.